Modified Lignin as an Environmentally Friendly Surfactant (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The effect of softwood sulphate lignin modified by its oxidation in alkaline medium on its behaviour at the air-water and oil-water interface, where rapeseed oil and technical fish fat oil served as the oil phase, was investigated. It has been found that, irrespective of the рН values of the water solution, the ability of the modified lignin to be adsorbed at the interfaces exceeds that of unmodified lignin, which is obviously caused by the pronounced differentiation of the hydrophilic and hydrophobic parts of the molecular structure in the oxidised lignin and the decrease in the content of the high-molecular fraction (Mw is greater than 1000) in it. At low concentrations (≤ 0.01 g/dl), the stabilising action of the modified lignin in the rapeseed oil-water emulsion is the same as that of sodium dodecyl sulphate. The enhanced surface activity of the oxidised sulphate lignin enables it not only to substitute the 30% of the mass of the commercial surfactant in the detergent composition for washing stainless steel plates, used during fish smoking, but also to upgrade its properties.